LANGUAGE ENVIRONMENT AS AN INVISIBLE CURRICULUM: RETHINKING ARABIC LEARNING THROUGH ALI AL-HADIDI’S LENS - Fairuz Subakir; Siti Nikmatul Rochma; Nur Fera Khalifah; Nuraeni Rahmawati; Ananda Rania Izzati (STKIP Pesisir Selatan, 2025)
This study investigates the language environment (bi'ah lughawiyyah) as an invisible curriculum in Arabic language learning through Ali Al-Hadidi's lens. Employing a Systematic Literature Review (SLR) based on the PRISMA framework, this study analyzed scholarly publications from 2020–2025 indexed in Scopus, Web of Science, DOAJ, and Google Scholar. The selected literature was examined using thematic synthesis and critical discourse analysis. The findings reveal that the language environment functions as an invisible curriculum that shapes learners' communicative competence, linguistic identity, disciplinary behavior, and cultural consciousness through everyday institutional practices. The study further demonstrates that Ali Al-Hadidi's educational thought implicitly reflects ecological and sociocultural approaches to language learning, emphasizing language habituation and collective interaction rather than grammar-centered instruction alone. This article contributes a new conceptual framework positioning the language environment as a curriculum ecosystem integrating formal instruction, social interaction, and institutional culture. The study concludes that the future of Arabic pedagogy in the post-method era depends on reconstructing immersive educational ecologies where language becomes a lived social and cultural experience.